Pengembangan Aplikasi Kamus Bahasa Biak Berbasis Android: Android-based Biak Language Dictionary Application Development - Sara Nelince Rumkabu; Julius Panda Putra Naibaho; Marlinda Sanglise (JISTECH: Journal of Information Science and Technology, 2023)
The development of information technology has so far advanced, and especially on smartphones, this makes smartphones a practical tool for learning media. Then an Android-Based Biak Language Dictionary Application was created. Preserving regional languages ​​is very necessary in the midst of very rapid technological developments, media dictionaries can be a solution for introducing the various regional languages ​​of Biak Numfor. The purpose of this research is to develop the Biak Regional Language Dictionary Application so that it can be managed properly by an administrator directly from the application. By utilizing the kodular tool, the Biak Regional Language Dictionary Application was developed with the results of the Biak Language Dictionary Application (KBB).